Influence of gibberellic acid on growth and quality of fenugreek (Trigonella foenum-graecum L.) - P K Chattopadhyay, C Tania, J N U Kumara, R Chatterjee, (Journal of Spices and Aromatic Crops, 2015)
Gibberellic acid (GA3) at 50 ppm, 75 ppm, 100 ppm and 125 ppm was sprayed to fenugreek at 40 and 60 days after sowing. GA3 @ 100 ppm promoted growth and produced highest yield (12.60 q ha-1), followed by GA3 @ 75 ppm (12.05 q ha-1) which, however, was at par with GA3 @ 100 ppm. Among quality parameters, carbohydrate was highest (45%) with GA3 @ 125 ppm whereas, crude protein content was highest (29.33%) with GA3 @ 75 ppm. The highest oleoresin content (0.3%) and highest essential oil content (2.8%) was recorded with GA3 @ 100 ppm.